Review and new data on the aphid fauna (Hemiptera, Aphidoidea) of the Socialist Republic of Vietnam with a description of a new genus and a new species of the family Hormaphididae - Stekolshchikov, Andrey V.; Novgorodova, Tatiana A. (Zootaxa, 2023)
An up-to-date information on aphid fauna (Hemiptera, Aphidoidea) of Vietnam based on literature data and original material is presented. The updated check-list of aphids includes 47 species, and also 15 species identified only to genus level. Protastegopteryx vietnamensis gen. nov., sp. nov. from Bambusa sp., collected in Cát Tiên National Park (Dong Nai Province), is described. The species is illustrated and its biometric data is provided. The described aphid genus is closely related to Astegopteryx Karsch, 1890. The taxonomic position of the genus is discussed.